2023
DOI: 10.1111/cns.14100
|View full text |Cite
|
Sign up to set email alerts
|

Marsdenia tenacissima extract prevents the malignant progression of glioma through upregulating lncRNA MEG3 and SFRP1‐dependent inhibition of Wnt/β‐catenin pathway

Abstract: Background/Aim Recent studies have highlighted the tumor‐suppressive effect of Marsdenia tenacissima extract (MTE) on human cancers. This research unveils the potential impact of MTE on glioma and ascertains the relevant molecular mechanisms. Methods Glioma cells were treated with MTE, with normal human astrocytes (NHAs) as controls. A battery of function experiments, including the CCK‐8 viability test, colony formation assay, scratch migration assay, and Transwell invasion assay, was executed to address the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…In addition, overexpression of miR-31 in these cells depletes several other antagonists of Wnt signaling that have potential miR-31 binding motifs, including SFRP1, SFRP4, and WIF-1, which are often silenced in human lung cancer [ 44 ]. Studies have shown that LncRNA MEG3 and SFRP1 can competitively bind to miR-542-3p [ 45 ]. Therefore, we inferred the competitive binding of LncRNA MEG3 and SFRP1 to miR-31 by dual luciferase assay in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of miR-31 in these cells depletes several other antagonists of Wnt signaling that have potential miR-31 binding motifs, including SFRP1, SFRP4, and WIF-1, which are often silenced in human lung cancer [ 44 ]. Studies have shown that LncRNA MEG3 and SFRP1 can competitively bind to miR-542-3p [ 45 ]. Therefore, we inferred the competitive binding of LncRNA MEG3 and SFRP1 to miR-31 by dual luciferase assay in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted frizzled‐related protein 1 (SFRP1) has been identified as a tumour suppressor gene that is commonly downregulated in human cancers 16–18 . Over‐expression of SFRP1 can significantly inhibit the proliferation of tumour cells by negatively regulating β‐Catenin 16,19 . However, the expression of SFRP1 is highly regulated by DNA methylation 18,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 , 18 Over‐expression of SFRP1 can significantly inhibit the proliferation of tumour cells by negatively regulating β‐Catenin. 16 , 19 However, the expression of SFRP1 is highly regulated by DNA methylation. 18 , 20 , 21 Generally, DNMTs regulate DNA methylation, with three common isoforms identified in humans: DNMT1, DNMT3a and DNMT3b.…”
Section: Introductionmentioning
confidence: 99%